2018
DOI: 10.3390/md17010006
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazine and Diphenylether Derivatives from Marine Algae-Derived Aspergillus versicolor OUCMDZ-2738 by Epigenetic Activation

Abstract: A chemical-epigenetic method was used to enhance the chemodiversity of a marine algicolous fungus. Apart from thirteen known compounds, (+)-brevianamide R ((+)-3), (‒)-brevianamide R ((‒)-3), (+)-brevianamide Q ((+)-4), (‒)-brevianamide Q ((‒)-4), brevianamide V ((+)-5), brevianamide W ((‒)-5), brevianamide K (6), diorcinol B (7), diorcinol C (8), diorcinol E (9), diorcinol J (10), diorcinol (11), 4-methoxycarbonyldiorcinol (12), two new compounds, (+)- and (‒)-brevianamide X ((+)- and (‒)- 2)), as well as a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, the same ECD cotton effects ( Figure 3 C) of 2 compared to 1 indicated that the absolute configuration of C-9 in 2 was consistent with that in 1 . This result suggested that within the used spectral window, the ECD cotton effects were mainly caused by the chiral center of C-9 in both compounds 1 and 2 , and it could also be confirmed by the experimental ECD data of (+)-brevianamide V and (−)-brevianamide V [ 35 ]. Thus, the absolute configuration of compound 2 was ascertained as (6 S ,9 S ).…”
Section: Resultsmentioning
confidence: 64%
“…Furthermore, the same ECD cotton effects ( Figure 3 C) of 2 compared to 1 indicated that the absolute configuration of C-9 in 2 was consistent with that in 1 . This result suggested that within the used spectral window, the ECD cotton effects were mainly caused by the chiral center of C-9 in both compounds 1 and 2 , and it could also be confirmed by the experimental ECD data of (+)-brevianamide V and (−)-brevianamide V [ 35 ]. Thus, the absolute configuration of compound 2 was ascertained as (6 S ,9 S ).…”
Section: Resultsmentioning
confidence: 64%
“…Brevianamides belong to a class of naturally occurring 2,5-diketopiperazine alkaloids, which are mainly produced by fungi of Penicillium and Aspergillus [6,9,32,35,36]. In this research, three pairs of new brevianamides ((±)- 1 –(±)- 3 ) were isolated and their relative configurations were elucidated according to the 1D, 2D NMR, HRESIMS, UV.…”
Section: Discussionmentioning
confidence: 97%
“…In 2019, a pair of enantiomers, (+)-and (−)-brevianamide X (95 and 96), was isolated from chemical-epigenetic cultures of A. versicolor OUCMDZ-2738 with 10 μmol/L fluinostat (SAHA). Compared to cultures in the same medium without SAHA, these two compounds were solely observed under SAHA condition (Liu et al 2019).…”
Section: Idps From the Fungal Genus Aspergillusmentioning
confidence: 89%